2022
DOI: 10.1177/09722629221087361
|View full text |Cite
|
Sign up to set email alerts
|

Customers’ Attitude Towards Vegan Products Consumption and Its Impact on Purchase Intension: An Indian Perspective

Abstract: Increasing environmental degradation, animal cruelty and health consciousness has drawn attention towards environment-friendly eating habits and adopting a vegan lifestyle. This study aims to explore the impact of health awareness, animal welfare, environmental concern and subjective norms’ antecedents on customers’ attitude towards the consumption of vegan products and its impact on purchase intention. By utilizing a structured questionnaire, data has been collected from 214 Indian respondents via Facebook ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Although, some studies reported no significant effects on organic purchases (Asif et al, 2018;Smith & Paladino, 2010; or food waste intentions (Tsai et al, 2020). For meat consumption, participants from Canada, Kuwait and India reported that their attitudes towards vegan products were significantly influenced by their environmental concerns (Bakr et al, 2023;Malik & Jindal, 2022).…”
Section: Theme 2: Testing An Extended Version Of the Tpbmentioning
confidence: 99%
“…Although, some studies reported no significant effects on organic purchases (Asif et al, 2018;Smith & Paladino, 2010; or food waste intentions (Tsai et al, 2020). For meat consumption, participants from Canada, Kuwait and India reported that their attitudes towards vegan products were significantly influenced by their environmental concerns (Bakr et al, 2023;Malik & Jindal, 2022).…”
Section: Theme 2: Testing An Extended Version Of the Tpbmentioning
confidence: 99%
“…Goyal et al (2020) explored the influence of environmental concerns on the adoption of vegan diets. Further, Malik and Jindal (2022) have focused on the adoption of vegan diets through societal and morally informed lenses. Examining veganism within this specific cultural context offers a nuanced understanding that might differ from studies conducted in the Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…According to a survey conducted by Rakuten Insights (2022), veganism is on the rise in India (estimated US $33.3 billion by 2030) with reasons such as animal welfare, vegetarian diet, food allergies, healthiness, environment, taste, and new food habits related trends. This healthy lifestyle‐linked inclination toward vegan food is primarily observed among urban Indian consumers but its wider acceptance cannot be ignored (Kautish & Sharma, 2020; Malik & Jindal, 2023). Given the rise in health awareness, sustainability‐driven popularity, and consumption of vegan food products in India, it is essential to research and establish the relationship between individual value drives (value orientation) and associated objects (nature) based on symbolic interactionism, for example, connectedness, feelings, love, or emotions (Antonetti & Maklan, 2014; Kautish & Sharma, 2019).…”
Section: Introductionmentioning
confidence: 99%